Contribuição à química dos compostos voláteis de Lippia alba (Mill) N. E. Brown e Pelargonium graveolens l’ Herit e atividade inseticida frente à Spodoptera frugiperda (J. E. Smith) - Niculau, Edenilson dos Santos (2011)
This work was divided into three parts focusing two main topics: the study of volatiles compouds of P. graveolens and the study of the essential oil of L. alba and its evaluation of insecticidal activity against Spodoptera frugiperda. The chapter 2 approuch the study of the volatile compounds of the leaves of P. graveolens extracted by dynamic headspace using Porapak Q® as adsorbent and in nature peat, a novel adsorbent in the extraction of plant volatiles, and the results were compared with those obtained by hidrodestilation. The results showed that hydrodistilation (HD) was more efficient for extracting linalool and citronellyl formate. While citroneol, geraniol and geranyl tiglate were obtained in greater quantity by dynamic headspace using in nature peat (HSD-T), isomenthone, 6,9- guaiadiene and - muurolene by headspace using Porapak Q® (HSD-P). The study of conversion proved that geraniol converts in linalool when geraniol is subjected to water vapor and high temperature, nevertheless a small ratio. This also prove, in parts, the high percentage of linalool obtained by HD compared to HSD-T and HSD-P. The chapter 3 approuch the study of the essential oils of 9 accessions of L. alba collected in 4 states of Brazil using statistical methods and checking the accessions with the best essential oil content. The statistical methods of hierarchical cluster analysis (HCA) and Principal component analysis (PCA) were used to prove the experimental data and confirmation of training groups. Three groups representatives of the three chemotypes were formed: Group I was characterized by linalool and 1,8-cineole; group II, by limonene and carvone; and group III by neral and geranial. In chapter 4 was approached the evaluation of insecticidal activity of the essential oils of P. graveolens (PEL-001) and L. alba (accessions LA-10, LA-22 and LA-57) and also of the main compounds (geraniol, linalool, 1,8-cineole, limonene, carvone) against S. frugiperda via topical aplication. The test of topical application showed that the essential oils of P. graveolens (PEL-001) and L. alba (accessions LA-10, LA-22, LA-57) showed acute toxicity against larvae of S. frugiperda, causing mortality of up to 100% at a dose 192 μg/larvae.